How has newspaper coverage influenced young Singaporeans' perception of the Hong Kong police siege of the Hong Kong Polytechnic University? - Xiao, Zibang (Nanyang Technological University, 2020)
Various newspapers have reported on the 2019-2020 Hong Kong protests, but there lacks a systematic analysis on the media effects of such press coverage. This paper thus aims to examine the effects of mass media on public perception, by focusing on the Hong Kong police siege of the Hong Kong Polytechnic University on 17 November 2019. Three articles from China Daily, The Guardian, and the South China Morning Post covering the same event are selected to test for any change in the stances of young Singaporean participants. Through the empirical data collected, this paper has found that 1) media from contrasting media systems reports the same event with different bias, and 2) participants do not all display the selective exposure effect as hypothesised. The reasons for the different media effects on individuals are explored.